(untitled) (Modern education and development, 2025)
Motivation, engagement, autonomy, and critical thinking are essential components of effective language learning, influencing learners’ ability to develop linguistic and cognitive skills. This article examines how these factors contribute to language acquisition, emphasizing the importance of fostering intrinsic motivation, creating engaging learning environments, promoting learner autonomy, and enhancing critical thinking skills. Drawing on theoretical frameworks such as Self-Determination Theory (SDT) and Self-Regulated Learning (SRL), the study highlights practical strategies for educators to implement in language classrooms. By integrating these elements, educators can support students in becoming more independent, reflective, and proficient language learners.